Covid-19 and its impact on Finnish public libraries - Haasio, Ari; Kannasto, Elisa (Qualitative and Quantitative Methods in Libraries, 2020)
The aim of this study was to contribute to understanding how public libraries in Finland managed the situation caused by the COVID-19-pandemic by answering two research questions: 1) What were the effects brought by the COVID-19-pandemic on the functions of the Finnish public libraries and their daily operations and 2) what kind of influence did the pandemic have on the library staff’s daily work and their feelings? Data were collected with a questionnaire responded by 251 library professionals. Also ten interviews were conducted among Finnish librarians. As a result, it was found that in some cases the libraries were able to innovate new forms of online services and the staff was able and keen to develop their skills in producing content on social media. In libraries where some or all the staff was temporarily laid off or their payroll was interrupted, the negative effect on motivation was evident.